Decay of chilli fruits in India during storage - MANOJ KUMAR and NARESH NARAYAN, B.K. PRASAD, DEEPA RANI SAHOO (Indian Phytopathology, 2002)
Stored chilli (Capsicum annuum) fruits collected from different parts of India exhibited varying degrees of decay with respect to discoloration and breaking of the pericarp, detachment of the pedicel and spore dust formation within the fruit. Altogether 67 spp. of fungi were isolated from the stored chilli fruits, 3 spp. belonging to the Phycomycotina, 11 spp. to the Ascomycotina and 53 to the Deuteromycotina. Aspergillus flavus, A. terreus, A. candidus, A. niger, A. sclerotiorum, Fusarium moniliforme [Gibberella fujikuroi], F. sporotrichioides, Syncephalastrum racemosum, Paecilomyces varioti and Penicillium corylophilum were commonly associated with decaying chilli fruits stored in humid regions. Capsaicin content was decreased due to fungal infection.